2022
DOI: 10.1186/s13643-022-01994-5
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for developing, piloting and disseminating the PRISMA-COSMIN guideline: a new reporting guideline for systematic reviews of outcome measurement instruments

Abstract: Background Systematic reviews of outcome measurement instruments are important tools in the evidence-based selection of these instruments. COSMIN (COnsensus-based Standards for the selection of health Measurement INstruments) has developed a comprehensive and widespread guideline to conduct systematic reviews of outcome measurement instruments, but key information is often missing in published reviews. This hinders the appraisal of the quality of outcome measurement instruments, impacts the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The indicators and respective instruments summarized in this review identified modifications along with age. However, the report or calculation of the related validity, feasibility, and repeatability of each of the instruments should be addressed in future studies, taking as a reference the, in-development, PRISMA–COSMIN guidelines [ 105 ]. This evaluation will allow for the selection of instruments with superior psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…The indicators and respective instruments summarized in this review identified modifications along with age. However, the report or calculation of the related validity, feasibility, and repeatability of each of the instruments should be addressed in future studies, taking as a reference the, in-development, PRISMA–COSMIN guidelines [ 105 ]. This evaluation will allow for the selection of instruments with superior psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…In this phase, we considered eight measurement proprieties for each self-report breastfeeding self-efficacy tool: content validity, structural validity, internal consistency, cross-cultural validity/measurement invariance, reliability, hypotheses testing for construct validity, criterion validity, and responsiveness (Elsman et al, 2022; Mokkink et al, 2006; Prinsen et al, 2018). The COSMIN manual includes two additional evaluation parameters: PROM development and measurement error.…”
Section: Methodsmentioning
confidence: 99%
“…More precisely, it consists of a comprehensive framework that provides a standardized and transparent way of evaluating the methodological quality of PROMs, as per the case of breastfeeding self-efficacy measurements. The COSMIN methodology includes a checklist that evaluates the methodological quality of PROMs across several measurement properties and allows researchers to assess the quality of PROMs in a standardized and comprehensive manner (Elsman et al, 2022; Mokkink, de Vet, et al, 2018; Mokkink et al, 2006; Terwee et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This IfR guideline would include all potentially relevant IfR elements and could be further supplemented with suggestions for an appropriate wording based on application examples. Developing such an IfR guideline is an iterative process and should be based on established methods like Delphi study, survey of experts, and iterative group discussions to reach consensus as applied for the development of other wellknown reporting guidelines [8, [22][23][24][25].…”
Section: Implications For Researchmentioning
confidence: 99%